Rare association of dens invaginatus with impacted mesiodens - A case report - Prashant B. Patil; Smitha G. Chaudhari; Ankit Goel; Pooja Agarwal (Elsevier, 2012)
Mesiodens is a supernumerary tooth occupying the position in the maxillary anterior region. This additional tooth structure may cause disturbance in eruption or position of the adjacent teeth. About 8-25% of supernumerary teeth in the anterior region erupt spontaneously. Un-erupted supernumerary teeth are incidentally identified on a routine radiographic examination. Dens invaginatus is a rare tooth malformation showing an in-folding of enamel and dentine of affected tooth sometimes extending deep into the pulp cavity and the root portion. We report a case of un-erupted mesiodens causing midline diastema of permanent teeth subsequently corrected following extraction of mesiodens. Dens invaginatus was identified affecting the un-erupted mesiodens.It is rare to find dens invaginatus associated with a supernumerary tooth and only 10 such instances of dens invaginatus affecting supernumerary teeth have been reported in the English literature.